Factors That Predispose Undergraduates to Mental Issues: A Cumulative Literature Review for Future Research Perspectives - Limone, Pierpaolo; Toto, Giusi Antonia (Frontiers in Public Health, 2022)
Distress and mental health issues among college students during Covid-19 is an emerging topic of study. The aim of this research work is to illustrate academic and social risk factors and how they prove to be predictors of anxiety and depressive disorders. The methodology used is a cumulative literature review structured over ten systematic phases, and is replicable. Showing considerable potential for cumulative research, the relevance of this study reflects the concern of the academic community and international governments. The articles selected range from categorization of disorders in relation to mental health, to reporting the condition of rhinestones and difficulties of students in university contexts. In conclusion, the research focusses upon predisposing, concurrent or protective factors relating to the mental health of university students, so that institutions can act on concrete dynamics or propose targeted research on this topic.